Sitting on all sides of the table? OECD’s role in Icelandic Education Policy 2030 - Gunnlaugur Magnússon; Berglind Rós Magnúsdóttir (Nordic Journal of Studies in Educational Policy, 2024)
The OECD is an inevitable force in contemporary education. This paper illustrates how the OECD affects recent education policy-making in Iceland with a particular focus on recent documents establishing the new Education Policy 2030 in Iceland and on OECD reports that directly relate to this policy. We illustrate the relationship between these documents both topically and chronologically and use Marilyn Strathern’s (2006) reasoning about policy making by bullet-points to understand these policy products. Our conclusions are that education policy 2030 is a clear step into a more Nordic tradition of policymaking, in terms of basing policy in previous works and official reports as well as increasing involvement by stakeholders. However, they are characterized by politically admirable, albeit lofty, formulations of ambitions and focus areas, rather than measurable, actionable and implementable policies. The OECD is given a great influence not only as a referential point and a tool to legitimate particular policies, but also a post-hoc policy-implementation adviser and auditor of the policy. Even though the OECD is asked for evaluation of the visionary policy and seems to be the solution to the perceived lack of professional procedure in Icelandic governance, the time-frame seems not to have allowed a thorough use of their advice.